Level Of Skilling Skills Speed Classic Categories Nature Living Students Dehasen University Bengkulu - W. Rahayu; Suwarni Suwarni; Martiani Martiani (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the level of rock climbing ability in the speed classic category of wall climbing. The subjects of this research are students who love nature at the Dehasen Bengkulu University. which amounted to 20 students where the fastest time for male students was 11.43 seconds while the fastest time for girls was 14.14 seconds. rock climbing ability in the speed classic category. Dehasen Bengkulu University students, as many as 2 students (10%) had a